Start with the substitution \(s = nu\). Show that \[\Gamma(x)\zeta(x) = \int _{ 0 }^{ \infty }{ { e }^{ -s } } { s }^{ x-1 }ds\left( \sum _{ n=1 }^{ \infty }{ { n }^{ -x } } \right) \] is equivalent to the integral \[\Gamma(x)\zeta(x) = \int _{ 0 }^{ \infty }{ \frac { { u }^{ x-1 } }{ { e }^{ u }-1 } du } .\]
Solution
Since the gamma function is a real number, we may treat the product as
Γ(x)ζ(x)=n=1∑∞∫0∞e−s(ns)x−1n1ds.
We let s=nu and ds=ndu, thus
Γ(x)ζ(x)=n=1∑∞∫0∞e−nuux−1du=∫0∞(e−u+e−2u+e−3u+...)ux−1du=∫0∞ux−1e−u(eu−1eu)du=∫0∞eu−1ux−1du.
Check out my other notes at Proof, Disproof, and Derivation
#Calculus
#Integration
#Series
#Derivation
Easy Math Editor
This discussion board is a place to discuss our Daily Challenges and the math and science related to those challenges. Explanations are more than just a solution — they should explain the steps and thinking strategies that you used to obtain the solution. Comments should further the discussion of math and science.
When posting on Brilliant:
*italics*
or_italics_
**bold**
or__bold__
paragraph 1
paragraph 2
[example link](https://brilliant.org)
> This is a quote
\(
...\)
or\[
...\]
to ensure proper formatting.2 \times 3
2^{34}
a_{i-1}
\frac{2}{3}
\sqrt{2}
\sum_{i=1}^3
\sin \theta
\boxed{123}
Comments
There are no comments in this discussion.